A poética do ruído em Ricardo Domeneck: intertexto, performance e mídias - Peixoto, Bárbara Pereira Bin Bispo (2013)
This paper aims to analyze the Noise Poetics which the contemporary poet Ricardo Domeneck proposes in his body of work. Using two reference works which the author considers to be unique and continuous: a cadela sem Logos (a dog without Logos, 2007) and Sons:Arranjo:Garganta (Sounds:Arrangement:Throat, 2009), as well as his online experimentations with video-poems and the oral production of poetry, as a base, it is possible to verify how these noises reveal themselves. The ways of accomplishing this include inter-textual relationships (through direct citations), performance (the presence of the bodies and voices of both the poet and audience), and the use of other modes of media for the publication and dissemination of his work. By discussing the relationships of both poet and tradition and of poet and new meanings formed in the present day, the first chapter analyzes the noise as revealed in the inter-textuality created by direct references to artists and to the works within many artistic spheres, such as literature, cinema, plastic arts, and music. It also analyzes their interference in the reader s construction of meaning and in the shift of attention caused by this process. In contrast, the second chapter focuses on the noise from the perspective of the performance and through the value given by Domeneck to oral production and to the body/voice presence of the author and reader/viewer in the process of reading poetry. The third chapter investigates the ways in which the noises accompany the close relationship between Domeneck s poetry and other arts and with the use of other media forms, aside from print, and how these are utilized in the transmission of his poems and as a mantra in their formation. Thus, one can perceive both that this noise will always appear as an element of transcendence and transformation and that current poets, such as Domeneck, will use this resource, since it neither complies to nor accommodates pre-established artistic expectations. Further, it proposes a redefinition of poetic concepts and expectations, to contemporary works in particular. Domeneck s noises, whether as indirect references to important authors and works, the mixing of languages, the fragmented enjabement, the body, the voice and the performance, or even the exploitation of other forms of medial and artistic support, assure a rupture between yesterday and today and between tradition and the new. From that it is possible to adequately form perceptions regarding the context and current needs. Therefore, it renounces all labels that suppress contemporary poetry.